2021
DOI: 10.1186/s11671-021-03566-3
|View full text |Cite
|
Sign up to set email alerts
|

All-metal terahertz metamaterial biosensor for protein detection

Abstract: In this paper, a terahertz (THz) biosensor based on all-metal metamaterial is theoretically investigated and experimentally verified. This THz metamaterial biosensor uses stainless steel materials that are manufactured via laser-drilling technology. The simulation results show that the maximum refractive index sensitivity and the figure of merit of this metamaterial sensor are 294.95 GHz/RIU and 4.03, respectively. Then, bovine serum albumin was chosen as the detection substance to assess this biosensor’s effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 46 publications
(53 reference statements)
1
20
0
Order By: Relevance
“…It is found that S(f 1 ) = 309 GHz/RIU, FOM(f 1 ) = 2.97 (RIU −1 ), and Q-factor(f 1 ) = 9.96 for the low-frequency resonant mode, while S(f 2 ) = 730 GHz/RIU, FOM(f 2 ) = 2.52 (RIU −1 ), and Q-factor(f 2 ) = 10.17 for the high-frequency resonant mode. Comparing these results with those most recently reported in the literature [13,23,24,26,27,32,33] (see Table 2), it could be concluded that the proposed dual-band THz MM sensor provides the highest sensitivity among the other analogous appliances. In addition, it enabled one to characterize identical samples at multi frequencies due to its two resonance modes, thereby increasing the selectivity and sensitivity of detection.…”
Section: Figuresupporting
confidence: 81%
“…It is found that S(f 1 ) = 309 GHz/RIU, FOM(f 1 ) = 2.97 (RIU −1 ), and Q-factor(f 1 ) = 9.96 for the low-frequency resonant mode, while S(f 2 ) = 730 GHz/RIU, FOM(f 2 ) = 2.52 (RIU −1 ), and Q-factor(f 2 ) = 10.17 for the high-frequency resonant mode. Comparing these results with those most recently reported in the literature [13,23,24,26,27,32,33] (see Table 2), it could be concluded that the proposed dual-band THz MM sensor provides the highest sensitivity among the other analogous appliances. In addition, it enabled one to characterize identical samples at multi frequencies due to its two resonance modes, thereby increasing the selectivity and sensitivity of detection.…”
Section: Figuresupporting
confidence: 81%
“…THz waves CST Studio Suite 2020 software was used to study the electromagnetic responses of the designed terahertz metamaterial and optimize the geometrical dimensions of the SMSRR structure [22]. In the simulation, the boundary condition was set as unit cell for X/Y directions to repeat the structure periodically in two directions, while it was set as open for the Z direction, which refers to the perfectly matched layer (PML) condition.…”
Section: Structure Design and Simulationmentioning
confidence: 99%
“…Thus, by placing the measured substances on the sensor’s surface, in contact with the metallic structural layer, we can measure and calculate the resonant frequency shift of the transmission or reflection spectrum relative to the characteristic spectrum of the metamaterial itself to accomplish substance identification [ 19 , 20 , 21 ]. Wang et al [ 22 ] proposed a terahertz biosensor based on all-metal metamaterial with a maximum refractive sensitivity of 294.95 GHz/RIU and assessed this sensor’s effectiveness by detecting the bovine serum albumin. Wang et al [ 23 ] proposed a metamaterial biosensor, which consisted of a metal elliptical split-ring resonator array with a subwavelength structure based on flexible thin film to extend the application of flexible metamaterial in the sensor field, which reached 243 GHz/RIU with a high Q-factor of 14.2.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in 2013, Wu et al [20] achieved a label-free, alkanethiol-functionalized, and a specific THz MM sensor for streptavidin-agarose (SA) by using the biological combination of biotin and streptavidin, and detected different concentrations of streptavidin using different redshifts of resonance frequency. Lately, various functionalized THz MM chips based on periodic hole arrays, metamaterials, absorbers, Fano resonances, and 2D materials have been employed for high-sensitivity sensing and accurate discrimination in biomedical detection of proteins [21], cancer cells [22], DNA mutations [23], viruses [24], and microorganisms [25]. For example, Yoon et al [26] demonstrated highly sensitive identification of viruses by comparing their dielectric permittivity.…”
Section: Introductionmentioning
confidence: 99%